PARTISIPASI PENDUDUK DALAM KONSERVASI DI SEGARA ANAKAN - Dede Sugandi (Metafora: Education, Social Sciences and Humanities Journal, 2020)
The Sagara Anakan region is meeting some estuaries are undergoing a process of sedimentation. Impact of siltation and sedimentation caused the emergence of new deltas that lead to legal and institutional issues of ownership of the delta in the area. The mayor problemof this study is how the steps to perform the maintenance and protection, maintenance and protection efforts extent to support sustainable development and the factors that lead to sedimentation in the Segara Anakan?. The main purpose of this study is to learn the steps to perform the maintenance and protection, maintenance and protection of analyzing the efforts and analyze the factors that lead to sedimentation in th earea of Sagara Anakan. Conservation, vegetative, mechanical and chemistry methods that must be done. Segara Anakan area that to be studied is the area that has geographical location between 108001'15,66"BT -109000'00" BT and 7001'12, 96"LS -7046'44,4" LS. Areas to be studied in this research is the population in the watershed that towards into Sagara Anakan region. Conservation will be related to the socio-economic life of the population in and around the river that towards into Sagara Anaka region. Conservation needs to be done mechanically, physically integrated with socio-economic empowerment sustainable population.